THE IMPACT OF TRADE ON CHILD LABOR: EVIDENCE FROM SELECTED SAARC AND ASEAN COUNTRIES - Rossazana Ab-Rahim; Bilal Tariq (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Past studies have tended to investigate the relationship between trade and child labor under the traditional trade theories, while assuming that the trade in homogenous goods and the results show inconclusive evidence of a relationship. Hence, it would be interesting to investigate the trade effects of differentiated goods on child labor in the setting of the new trade theory. This study attempts to investigate the trade-induced child labor effects (selection, scale and technique effects) in selected Asian countries over the period from 1999 to 2013. The countries consist of the major South Asian Association for Regional Cooperation (SAARC) countries, namely: Bangladesh, India, Pakistan, Nepal, and Sri Lanka and selected ASEAN countries, namely: Cambodia, Indonesia, the Philippines, and Thailand, where child labor is most common. The results of this study confirm that the total impact of trade on child labor also needs to account for the selection effect, in addition to the scale and technique effects. The findings imply trade liberalization hampers the child labor market in the context of the trade in differentiated goods.